Multiple role stress, burnout, and purpose in life among female counselors - Vergara, Maria Belen (1999)
Eighty counselors participated in a study which sought to determine the difference between single and married female counselors in terms of multiple role stress, burnout, and purpose in life, and the relationship between burnout and purpose in life. Measures used were Maslach Burnout Inventory, Purpose in Life, and a questionnaire on priority roles, hours per week devoted to work and family roles, subjective estimate of multiple role stress, and nature of concerns and coping with multiple roles. Results revealed that married female counselors experienced multiple role stress more often than single counterparts. Married counselors placed higher priority on family roles than work role, spent more time performing family roles, and had more home-related concerns as compared to single counselors. Both groups coped with multiple role stress through social and religious activities. Both groups reported low emotional exhaustion and depersonalization, high personal accomplishment, and definite purpose in life. The findings also showed that purpose in life correlates negatively with emotional exhaustion and depersonalization, and correlates positively with personal accomplishment. Exploring multiple role stress from the perspectives of full-time homemakers and career women, women in professional and clerical positions, and men and women among dual-earner couples are potentially fruitful avenues for future research.
Includes bibliographical references (pages 122-126).